Peran Front Office Staff dalam Menunjang Kepuasan Tamu serta Membangun Citra Positif Hotel: Studi Kasus Grand Edge Hotel Semarang - Benedectta Arsenia Nanda Hardian; Julian Andriani Putri (Journal of Education, Humaniora and Social Sciences (JEHSS), 2026)
This article aims to explore the role of front office staff in supporting guest satisfaction and building a positive hotel image. The study focuses on how front office service practices at Grand Edge Hotel Semarang influence guest experiences and perceptions of hotel quality. To approach this issue, the study refers to service quality theory, the SERVQUAL dimensions, and the hospitality concept emphasizing staff responsiveness, empathy, and professionalism. Data were collected through semi-structured interviews with managers, supervisors, receptionists, and guests, participatory observations of daily front office activities, and internal hotel documentation, and analyzed qualitatively using thematic analysis. The study concludes that front office staff play a strategic role in creating a satisfying guest experience through warm greetings, prompt handling of requests and complaints, and accurate information delivery. Professional and empathetic interactions not only fulfill functional guest needs but also strengthen the hotel’s positive image, enhance loyalty, and reinforce reputation and competitiveness. Consistent implementation of SOPs, routine supervision, and ongoing training are key factors in maintaining high-quality front office services. These findings can serve as a reference for other hotels to optimize the front office’s contribution to guest satisfaction and positive hotel image.